Usability and Performance Evaluation of a Mobile Application for Learning PID Controllers: A Case Study with Engineering Students - Chamorro Atalaya, Omar (2025)
In the academic field, especially in contexts with limited technological resources, it is essential to provide tools that facilitate both the theoretical understanding and the practical application of PID controllers. This study evaluates the usability and performance of TempRes ControlSys Simulator, a mobile application developed to enhance practical learning of automatic control. Through a non-experimental case study, the User Experience Questionnaire (UEQ) was applied to assess the perception of usability, as well as BlazeMeter to analyze performance. The results reflect a moderate usability of the application, with 60% of the students highlighting its clarity, efficiency, and precision. In terms of performance, the results show that the mobile application responded optimally to the expected demand within the case study. It is concluded that the mobile application represents a viable and accessible alternative in educational environments with technological limitations, favoring inclusion by facilitating access to practical simulation tools. Future research should integrate external sensors for real-time signal acquisition, allowing its application in real scenarios such as the handling of robotic arms or the automatic orientation of solar panels, reinforcing the connection between simulation and experimentation in mechanical and electrical engineering students.